CALLUS INDUCTION AND PHYTOCHEMICAL CHARACTERIZATION OF Cannabis sativa CELL SUSPENSION CULTURES - Tri Joko Raharjo; Ogbuadike Eucharia; Wen-Te Chang; Robert Verpoorte (Universitas Gadjah Mada, 2006)
Callus of Cannabis sativa has been successfully induced from C. sativa explants and seedings. It seems that flowers are the best explant for callus induction and induction under light also give better results than induction in dark. Four cell culture lines were established from flower induced callus. Phytochemical profiles of C. sativa suspension cell cultures were investigated using HPLC and 1H-NMR. Cannabinoids and phenolic compounds related to cannabinoids such as flavonoids could not be found in the cell suspension cultures and there is no major chemical difference between the cell lines though they can visually be distinguished by their colors. Only in one cell line some aromatic compounds in the water/methanol extract could be observed in the 1H-NMR. Further investigations showed that none of these compounds are flavonoids. It seems that lack of cannabinoids in the cell cultures is related to lack of polyketide synthase activity.